Research on pulse width model of optical signal based on effects of combined physical impairments - Ji-jun ZHAO; Kun GUO; Zhi-hua LI; Li-rong WANG; Wen-yu ZHAO (Tongxin xuebao)
For the accurate assessment of physical impairments,the suppression or enhancement effect of self phase modulation (SPM) on group velocity dispersion(GVD) were analyzed.Then,a pulse width model based on their combined effects on signal distortion was proposed.This model considered the effects of combined physical impairments,and it was applied in the simulation of the impairment-aware routing and wavelength assignment(IA-RWA) algorithm.The results indicate that comprehensive consideration of the effects caused by combined physical impairments is conductive to accurately avoid more serious physical impairments during routing and reduces blocking rate.